New progress in tumor treatment based on nanoparticles combined with irreversible electroporation. Issue 10 (5th August 2022) - Xu, Lei; Xie, Liting; Fang, ChengYu; Lou, WenJing; Jiang, Tianan
Abstract: Nanoknife is a new tumor ablation technology. It forms nano permanent perforation on tumor cells by releasing high‐voltage pulses, destroying the intracellular balance and making cells apoptosis rapidly. So nano knife is also known as irreversible electroporation (IRE). IRE ablation technology and nanoparticles (NPs) have unique advantages in tumor treatment. Relevant studies have confirmed that NPs can enhance the effect of IRE ablation, expand the ablation boundary and reduce the threshold intensity of tumor cell perforation. Moreover, IRE combined with the drug‐loaded NPs can synergize tumor immunotherapy. Thus, the combination of NPs and IRE has broad research prospects. This paper reviews the mechanism of tumor treatment with NPs combined with IRE and discusses the future challenges and opportunities of combining these two technologies. Abstract : Irreversible electroporation (IRE) is a new tumor ablation technology. It forms nano permanent perforation on tumor cells by releasing high‐voltage pulses, destroying the intracellular balance and making cells apoptosis rapidly. Relevant studies have confirmed that nanoparticles can enhance the effect of IRE ablation. This paper reviews the mechanism of tumor treatment with nanoparticles combined with IRE and discusses the future challenges and prospects of combining these two technologies.